Isolation and quantitative estimation of diesel exhaust and carbon black particles ingested by lung epithelial cells and alveolar macrophages in vitro - Rajiv K. Saxena; M. Ian Gilmour; Michael D. Hays (BioTechniques, 2008)
A new procedure for isolating and estimating ingested carbonaceous diesel exhaust particles (DEP) or carbon black (CB) particles by lung epithelial cells and macrophages is described. Cells were incubated with DEP or CB to examine cell-particle interaction and ingestion. After various incubation periods, the cells were separated from free extracellular DEP or CB particles by Ficoll density gradient centrifugation and dissolved in hot sodium dodecyl sulfate detergent. Insoluble DEP or CB residues were isolated by high-speed centrifugation, and the elemental carbon (EC) concentrations in the pellets were estimated by a thermal-optical-transmittance method (i.e., carbon analysis). From the EC concentration, the amount of ingested DEP or CB could be calculated. The described technique allowed the determination of the kinetics and dose dependence of DEP uptake by LA4 lung epithelial cells and MHS alveolar macrophages. Both cell types ingested DEP to a similar degree; however, the MHS macrophages took up significantly more CB than the epithelial cells. Cytochalasin D, an agent that blocks actin polymerization in the cells, inhibited approximately 80% of DEP uptake by both cell types, indicating that the process was actin-dependent in a manner similar to phagocytosis. This technique can be applied to examine the interactions between cells and particles containing EC and to study the modulation of particle uptake in diseased tissue.